2013
DOI: 10.1111/j.1365-2265.2012.04467.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymic neuroendocrine tumour in multiple endocrine neoplasia type 1: female patients are not rare exceptions

Abstract: Summary Objective Thymic neuroendocrine tumour (Th‐NET) occurs in 2–5% of patients with MEN1 and has high malignant potency accompanying recurrence and distant metastasis. While Th‐NET is recognized to develop predominantly in men and heavy smokers, a number of female patients have been reported in the literature. The objective of this study is to clarify the clinical features of MEN1 patients with Th‐NET using database analysis. Design/Patients Clinical data of patients with Th‐NET were extracted and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…Approximately one-fifth of all thNETs are MEN1-related (Teh et al 1997), therefore the diagnosis of a thNET should always prompt further evaluation of a possible underlying MEN1 syndrome (de Laat et al 2012). Mean age at diagnosis of thNETs in MEN1 is 39-47 years (Teh et al 1997, Gibril et al 2003, Ferolla et al 2005, Goudet et al 2009, Sakurai et al 2013. In series from USA, Europe, and Australia 95-100% of the patients are male (Teh et al 1997, Gibril et al 2003, Ferolla et al 2005, Goudet et al 2009), whereas in a recent Japanese series 64% of thNETs occurred in males (Sakurai et al 2013).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one-fifth of all thNETs are MEN1-related (Teh et al 1997), therefore the diagnosis of a thNET should always prompt further evaluation of a possible underlying MEN1 syndrome (de Laat et al 2012). Mean age at diagnosis of thNETs in MEN1 is 39-47 years (Teh et al 1997, Gibril et al 2003, Ferolla et al 2005, Goudet et al 2009, Sakurai et al 2013. In series from USA, Europe, and Australia 95-100% of the patients are male (Teh et al 1997, Gibril et al 2003, Ferolla et al 2005, Goudet et al 2009), whereas in a recent Japanese series 64% of thNETs occurred in males (Sakurai et al 2013).…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of thNETs among MEN1 patients is 2-8% (Teh et al 1997, Burgess et al 1998b, Gibril et al 2003, Goudet et al 2011, Sakurai et al 2013. Approximately one-fifth of all thNETs are MEN1-related (Teh et al 1997), therefore the diagnosis of a thNET should always prompt further evaluation of a possible underlying MEN1 syndrome (de Laat et al 2012).…”
Section: Epidemiologymentioning
confidence: 99%
“…Two complementary methods were used to quantify intrafamilial correlations. As expected from the existence of familial clusters of thNETs in the literature (11,12,14), a strong genetic component was identified regarding thNETs. While these tumors are diagnosed in 5-7% of MEN1 patients, the first series of genotyped patients with thNETs revealed that 15/150 cases were familial (3,11,12,14,18).…”
Section: Discussionmentioning
confidence: 58%
“…This strategy is well known for thNETs because thNET clusters were evidenced early. The right imaging tool to detect this tumor is still debated because yearly CT scans of the chest could be harmful, but it is known and accepted that we must pay particular attention to the relatives of patients with thNETs (11,12,14,15). Pituitary adenomas and adrenal tumors are underdiagnosed tumor types in MEN1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation